Märchen auf einen Blick - Schwind, Moritz von,Pocci, Franz,Speckter, Otto,Grimm, Jacob,Bechstein, Ludwig,Hauff, Wilhelm (Kinderbuchverl., 1989)
891718 <dt.>
PRIORITY 2
Keywords: Anthologie; Kinderbuch; Bildband